Evaluation of 5 hybrid yams for dry season yam production in lowland areas - Ikeorgu, J.; Asiedu, Robert (2006)
A two year trial was conducted at the inland valley of the National Root Crop Research Institute, Umudike during the dry season of 2003/2004 and 2004/2005. The purpose was to evaluate the suitability of five hybrid yam clones of dry season yam production. The yams were planted in manually made ridges and laid out in RCB design in three replicates. Fresh yam tuber yield 22.6t/ha; 21.8t/ha: 19.1 t/ha and 18.1 t/ha were respectively achieved from TDr 95/18949: Tdr 97/00925; TDr 03/00193 and TDR 95/19158. These matured earlier and yielded higher than the local best cultivar Ekpe (12.2 t/ha). Farmers that have farmlands that are hydromorphic during the dry season or have irrigation facilities, are encouraged to utilize such lands for off-season yams production so as to ensure year round fresh yam supplies in the market in view of the current pressure on cassava as a staple.